The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jfpp.12589
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Recovery of Protein and Polysaccharide from Abalone (Haliotis discus hannai Ino) Gonad Using Enzymatic Hydrolysis Method

Abstract: Abalone gonad, the major processing by-product, contains many useful components beneficial to health such as polysaccharides, proteins (peptides) and lipids. In the present study, the distribution of dry matter, protein, polysaccharide and lipid between the three centrifuged phases (sludge, aqueous and lipid phases) of the hydrolysates from abalone (Haliotis discus hannai Ino) gonad was investigated to reveal the possibility for the simultaneous recovery of the valuable components. Before hydrolysis, the dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Abalone is a food containing several nutrients such as proteins, polysaccharides, and fatty acids, and its components show bioactivities involving inflammation, oxidation, and tumor protective activities; therefore it is widely consumed in Asian countries [16][17][18][19][20][21]. The present study focused on the viscera, which contains various pigments between male (brown) and female (green) viscera as by-product of abalone.…”
Section: Preparation Of Active Fraction From Amv Via Bioactivity-guid...mentioning
confidence: 99%
See 1 more Smart Citation
“…Abalone is a food containing several nutrients such as proteins, polysaccharides, and fatty acids, and its components show bioactivities involving inflammation, oxidation, and tumor protective activities; therefore it is widely consumed in Asian countries [16][17][18][19][20][21]. The present study focused on the viscera, which contains various pigments between male (brown) and female (green) viscera as by-product of abalone.…”
Section: Preparation Of Active Fraction From Amv Via Bioactivity-guid...mentioning
confidence: 99%
“…Abalone viscera, which is the by-product that is often discarded as industrial waste, may account for approximately 15 25% of the total body weight of raw abalone and is used to prepare Jeonbokjuk in South Korea. It contains proteins, polysaccharides, and fatty acids and exhibits tumor, inflammation, oxidation protective effects [16][17][18][19]. We previously reported that the active fraction derived from abalone male viscera (AMV) with anti-oxidant activities shows inhibitory effect via inhibition of lipopolysaccharide (LPS)-induced macrophage activation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Abalone viscera accounts for about 15–25 % of the total body weight of abalone ( Zhou et al, 2012 ) and is often discarded during processing. Abalone viscera are rich in protein which can be used as precursors of bioactive peptides ( Zhou et al, 2016 ). Previous studies have shown that abalone viscera protein hydrolysate have antioxidant (Hu, Yang, He, Wei, Wu, Xiong, et al, 2022 ), anti-inflammatory ( Suleria, Addepalli, Masci, Gobe, & Osborne, 2017 ), and antitumor ( Chen, Wei, Ye, Chen, & Weng, 2018 ) effects, and some iron-chelating peptides have been identified from the abalone viscera hydrolysates, which might be used as ingredients in function foods ( Wu, Jia, Wen, Yu, Zhao, & Hu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Mexico alone, approximately 42.9–71.5 t of viscera are generated from an annual fishery production of 286 t 13 . Therefore, there is potential for the valorization of abalone viscera byproducts, as they are a rich source of protein and can be used as precursors of bioactive peptides 14 . There is substantial evidence of bioactive compounds in abalone, such as peptides and polysaccharides, that exhibit various bioactivities, including nutraceutical properties 15 and pharmacological properties 16 27 .…”
Section: Introductionmentioning
confidence: 99%